The Wiley handbook of gender equity in higher education - Niemi, Nancy S.; Weaver-Hightower, Marcus B. (Wiley Blackwell, 2021)
With this enlightening handbook, you can review the thinking of leading researchers on the current intersection of gender and higher education. The Wiley Handbook of Gender Equity in Higher Education provides an in-depth look at education's complicated relationships with, and in some cases inadequate fostering of, gender equity. The collection offers a bold picture of research into the subject. It also projects future paths of exploration, inquiry, and action for gender equity.